HYDROGEOLOGICAL MODELING USING MODFLOW TO ESTIMATE THE GROUNDWATER INFLOW INTO PIT QZ FOR PUMPING PLAN AT DIFFERENT MINE DEVELOPMENT STAGES - Ramadhona, Yudanta Arba; Fauziyyah, Fithriyani; Maulana, Achmad; Yusuf, Alfian (Prosiding Temu Profesi Tahunan PERHAPI, 2023)
An excavation activity in open pit mining often means penetrating the local or regional groundwater table into the pit which may cause water in a rush into the excavation location. In case that the host rock is significantly permeable, it can become a big problem for mining excavation operations. Consequently, in order to avoid excessive waterlogging, a good dewatering strategy is required by simulating and estimating groundwater inflow. Pit QZ geologically located in the tertiary Pasir sub- basin, are multi-seam deposits within the Miocene age Warukin Formation which is mainly composed of coal, mudstone, and interbedded fine sandstone. The hydrogeological model was built by MODFLOW both conceptual and numerical modeling based on hydrogeology parameters data taken from field observation and study literature for modeling groundwater inflow into the pit at different mine development stages. This study uses groundwater evapotranspiration and other hydrologic features, such as observation wells and rivers, as boundary conditions. Based on geological conditions of Pit QZ, the hydrostratigraphy consists of sandstone as aquifers, mudstone and coal as aquitards with hydraulic conductivity values in aquifer of 1 x 10-5 m/s and aquitard of 1 x 10-8 m/s. The groundwater budget result revealed that the mining area would receive net groundwater inflows of 8,636 m3day-1 in the initial stages of development. The net groundwater inflow would be 16,605 m3day- 1 and 22,219 m3day-1 in the second and third development stages, respectively. The result of the model can be used to plan optimal groundwater pumping and the possible locations to dewater the groundwater for safe mining at different mine development stages. This hydrogeological model can also be integrated with the geotechnical model to characterize the groundwater table for the purposes of slope stability analysis because of its effect on pore water pressure within the slope material.